Dancing with giants : China, India, and the global economy - Winters, L. Alan; Yusuf, Shahid, 1949- (World Bank e-Library., 2007)
China is now the world's fourth largest economy and growing very fast. India's economic salience is also on the rise. Together these two countries will profoundly influence the pace and nature of global economic change. Drawing upon the latest research, this volume analyzes the influences on the rapid future development of these two countries and examines how their growth is likely to impinge upon other countries. It considers international trade, industrialization, foreign investment and capital flows, and the implications of their broadening environmental footprints. It also discusses how th.